Simple Graphical Pre- and Post-Processor for 3-D Magnetotelluric Inversion - Tanaka, Ryo (Journal of disaster research, 2022)
To understand a field of volcanic activity, a survey on the Earth’s subsurface structure is helpful. In particular, a magnetotelluric survey can image the subsurface structure necessary for volcanic disaster prevention because it is sensitive to high-temperature areas and areas where fluid and clay minerals exist. In 3-D magnetotelluric inversion using the data observed near volcanoes and the coastline, the topography and sea around the survey area need to be considered. Therefore, constructing a mesh of the analysis area by automatically using topography and bathymetry data is necessary. Additionally, the estimated subsurface structure should be compared to the sources of variation estimated from other physical observations, such as earthquakes, ground deformation, and changes in the geomagnetic total field, for interpretation. This study introduces a simple and easy-to-operate graphical pre- and post-processor developed to support the resistivity structure analysis of a volcano and the nearby coastline. In the developed software, the pre-process indicates the mesh construction, and the post-process indicates result derivation, file construction for the sensitivity tests, and file exportation to compare the inversion results with other measured quantities. This pre- and post-process can be performed easily on the same window of the software.